Sistem Pengendali Inventori Supply Chain Dengan Pendekatan Probabilitas Pada Industri Pakaian - ., Mustafid; Sabila, Alzena Dona; ., Suryono (Universitas Diponegoro, 2018)
Inventory control systems have an important role in supply chain management to control process of production, inventory and distribution of products in accordance with rapidly changing consumer demand. The research aims to develop inventory control system on supply chain that can manage the number of production and supply of products based on variables of consumer demand and lead time. Supply chain inventory control systems are designed using model of supply chain inventory control within the information system framework. Model of inventory control using variable of demand lead time is designed by probability approach. Input to the system are data of demand and lead time sent by retail. The results of research provide theory of supply chain inventory control system with probability approach, especially on developing the theory of probability distribution for combined variables from two random variables of normal distributed. Inventory control system used to determine safety stock and reorder point as the basis for determining the replenishment stock. Furthermore by the system, supply chain management can manage the estimation of production number, and manage inventory and stock number of products in warehouse, supplier and retail in accordance with the consumer demand.